The production process of spring wheat plants in the system of biological agriculture - N. N. Shuliko; O. A. Yusova; A. A. Kiselyova; E. V. Tukmacheva; V. S. Yusov; E. V. Kubasova; I. A. Korchagina; A. Yu. Timokhin (Труды по прикладной ботанике, генетике и селекции)
Background. Analyzing photosynthetic processes in a plant makes it possible to opine on the rate of its growth and development. In addition to classical physiological techniques, an interest is currently growing in spectrometry, which provides a realtime opportunity, based in the values of vegetation indices, to find out whether a plant is under stress or not.Materials and methods. Spring bread wheat cvs. ‘Omskaya 42’, ‘Omskaya 44’, and ‘Tarskaya 12’, and spring durum wheat cv. ‘Omsky Korall’ were analyzed in Western Siberia. Seeds were bacterized before sowing with an inoculant of diazotrophs belonging to Arthrobacter mysorens 7 and Flavobacterium sp.Results. Identification of increased plant growth and development rates is possible with the following vegetation indices in the ear emergence phase: TCARI = 27.32, MCARI = 106.4, SPAD = 40.6, CPHLT = 25.02, CPHLB = 14.5, CPHLA = 8.46, and CCI = 27.5, and those in the grain filling phase: CPHLT = 10.4, CPHLB = 7.2, and CPHLA = 4.7. The highest nitrogen-fixing activity level was observed in the rhizosphere of bread wheat cv. ‘Omskaya 42’ and durum wheat cv. ‘Omsky Korall’, amounting to 150.7–322.0 and 140.0–393.0 nM C2H4/100 g of soil, respectively, with the introduction of Arthrobacter mysorens 7 bacteria, and 149.0–281.0 and 86.2–554.5 nM C2H4/100 g of soil, respectively, with Flavobacterium sp.Conclusion. Consistently high values of the associative nitrogen fixation process were recorded in the variants involving bacterization of wheat seeds of cvs. ‘Omskaya 42’ and ‘Omsky Korall’ with the stimulating fungicide drugs Mizorin and Flavobacterin. According to the values of the TCARI and SPAD indices, it is possible to opine on the potential nitrogen-fixing activity and the yield of a cultivar.